Bilateral antrochoanal polyp: a rare entity - Kumari, Nisha; Shivayogimath, Kathyayini N.; Singh, Roohie; Sengupta, Prashant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Antrochoanal polyps (ACPs) are benign polyps that arises from inflamed and edematous mucosa of maxillary antrum. They arise most commonly from posterior wall of maxillary sinus. They occur more commonly in children and young adults without any sex predilection. The etiopathogenesis of ACPs is not clear but chronic sinusitis and allergy have been implicated. Patient usually present with nasal obstruction, may also have symptoms of epistaxis, rhinorrhoea, foreign body sensation. The diagnosis of the disease is done based on endoscopic examination of nasal cavities, computed tomography (CT) scan findings, and histopathologic results. ACPs are usually unilateral but can be bilateral in extremely rare cases. Based on adequate history and clinico-radiological examination misdiagnosis can be avoided which may lead to no improvement of symptoms and mandating revision surgery. Treatment of ACPs is always surgical. Functional endoscopic sinus surgery (FESS) and powered instrumentation during FESS is safe and effective method. Treating surgeon should focus on detecting the exact origin and extent of polyp to prevent recurrence. We herein presented extremely rare case of bilateral ACP in a 46 years female.